VD_FINDINFO HC / 2010 / 533 vom 23. August 2010 - VD Tribunal cantonal (2010)
JUGEMENT DE DIVORCE, ACTION EN MODIFICATION, DROIT DE GARDE, OBLIGATION D'ENTRETIEN | 134 CC, 145 al. 1 CC, 273 CC, 286 al. 2 CC, 451 ch. 3 CPC, 452 al. 2 CPC